Impact of Online Shopping on the Purchase Behavior of Consumers in Chennai City - A.VARADARAJ; D.CHARUMATHI (Eastern European Journal of Regional Studies)
Online shopping or e-shopping is a form of electronic commerce which allows consumers to directly buy goods or services from a seller over the Internet using a web browser. The proliferation of online group buying websites is changing marketing strategies and buyers' habits without doubt. The study focuses on the impact of online shopping on the purchase behaviour of consumers in Chennai city. Questionnaire was used to collect the primary data. The sample size of the study was 150 and the sample design adopted was convenience sampling. This paper tried to find out the impact of online market towards purchase behaviour of consumers and gives suggestions to improve the same.